Sediments, morphology, and sedimentary processes on continental shelves : advances in technologies, research, and applications - Hill, Philip R.; Li, Michael Z.; Sherwood, Christopher R. (Special publication / International Association of Sedimentologists, 2012)
The application of multibeam and sediment transport measurement technologies and the adoption of multi-faceted research methodologies have greatly advanced our understanding of the sedimentary processes on continental shelves in the last decade